A Development of Attitudes of Religious Moderation Through Rewang Culture in Generation Z in Boyolali Gajah Demak Village - Khoirunnisak, Itak; Mintarsih , Widayat; Algifahmy, Ayu Faiza (LPPM Institut Agama Islam Diniyyah Pekanbaru, 2024)
The aim of this research is to examine and describe how rewang culture can be a way to develop an attitude of religious moderation in generation Z. The research method used is a qualitative approach, as well as interviews and observation, as data collection techniques. Qualitative research aims to understand social phenomena through descriptions of words and language. This method involves in-depth interviews and observations with informants. Thus, qualitative research allows researchers to understand human concepts, behavior and perceptions holistically. The results of this research show that rewang culture can be used as a way to develop attitudes of religious moderation in generation Z in Boyolali Village, Gajah District, Demak Regency, Central Java. Through rewang, generation Z will learn how to appreciate the various differences that exist in society. Starting from differences in social status, differences in beliefs, and other differences. Rewang culture has an important role in developing an attitude of religious moderation in generation Z. By inviting generation Z to actively participate in the implementation of rewang, we can create a more harmonious and united society. The existence of rewang also provides a sense of family and comfort in society.